2011
DOI: 10.1126/scitranslmed.3002761
|View full text |Cite
|
Sign up to set email alerts
|

Age-Related Intimal Stiffening Enhances Endothelial Permeability and Leukocyte Transmigration

Abstract: Age is the most significant risk factor for atherosclerosis; however, the link between age and atherosclerosis is poorly understood. During both aging and atherosclerosis progression, the blood vessel wall stiffens owing to alterations in the extracellular matrix. Using in vitro and ex vivo models of vessel-wall stiffness and aging, we show that stiffening of extracellular matrix within the intima promotes endothelial cell permeability—a hallmark of atherogenesis. When cultured on hydrogels fabricated to match… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

33
424
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 343 publications
(466 citation statements)
references
References 54 publications
33
424
2
Order By: Relevance
“…Various diseases, such as cancer and fibrosis, that are accompanied by abnormal vascular permeability also exhibit altered tissue mechanics (for example, increased stiffness) 4,13,[18][19][20] . We, therefore, explored whether changes in mechanical interactions between cells and ECM might regulate vascular permeability by culturing lung human microvascular endothelial (L-HMVE) cells on fibronectin-coated polyacrylamide gels with different stiffness (Young's moduli of 150-35,000 Pa) (ref.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Various diseases, such as cancer and fibrosis, that are accompanied by abnormal vascular permeability also exhibit altered tissue mechanics (for example, increased stiffness) 4,13,[18][19][20] . We, therefore, explored whether changes in mechanical interactions between cells and ECM might regulate vascular permeability by culturing lung human microvascular endothelial (L-HMVE) cells on fibronectin-coated polyacrylamide gels with different stiffness (Young's moduli of 150-35,000 Pa) (ref.…”
Section: Resultsmentioning
confidence: 99%
“…Strikingly, the potent effects of endotoxin on pulmonary vascular permeability can be prevented by manipulating ECM structure, and hence, this mechanical control pathway could potentially lead to new approaches to clinical therapy in the future, in addition to providing greater insight into how changes in pulmonary microvascular structure influence organ pathophysiology. Changes in LOX activity levels that alter tissue structure and ECM mechanics contribute to many pathological processes that are characterized by abnormal vascular permeability, including fibrotic disorders 33,39 and cancer progression 13,37 , as well as cardiovascular diseases 20,40,41 . Our results show that ECM mechanics need to be regulated tightly to maintain optimal cell-cell junctional integrity and pulmonary vascular function in normal lung.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A previous study by Choi et al has shown that using hydrogels to mimic the stiffness of young and aging intima demonstrates that the aging process increases the permeability of an endothelial cell monolayer and disrupts cell-cell junctions by activating the Rho-dependent signaling pathway to upregulate cell contractility. 64 …”
Section: Cellular Response To Ecm Stiffness During Tissue Homeostasismentioning
confidence: 99%
“…Beyond CCM disease, endothelial ROCK activity has been postulated as a central mechanism in the aging brain. 33 Thus, our studies of brain permeability optimized and clarified in CCM patients may motivate future research and find broader biomedical applications in the clinical setting.…”
Section: Age and Vascular Permeability In Brain And Lesionsmentioning
confidence: 99%